Literary work and its audience - István Nyomárkay (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2011)
The study of functions of German language elements, primarily separate words (lexical elements) and fixed expressions, proves that they are an integral part of the text, play a specific role in communication and illustrate a variety of contexts within a play. Specific examples are used to present the role of German vocabulary, i.e. for the purpose of making overstatements, pointing out certain circumstances, exaggeration, etc. The text and its analysis proves that the understanding of a literary work is closely connected to the historical, cultural and language education of its readers.